Virtual consumption: A review of digitalization's “green” credentials - Hynes, Mike (Frontiers in Sustainability, 2022)
The unprecedented development, growth, and widespread pervasiveness of digital Information Communication Technologies (ICTs) have coincided with ever-increasing levels of consumption and the climate emergency. Digital ICTs, once lauded for their potential to dematerialise society, are now imposing additional burdens on the planet. The widespread consumption of personal electronics continues to grow at an enormous rate, while recycling of the scarce rare-earth minerals that are crucial to their development is negligible. As digital technologies become ubiquitous, the need for additional energy to power our ever-increasing number of digital devices and services must also keep pace. Moreover, despite their public veneer as progressives, digital tech companies are collaborating with fossil fuel companies to render oil and gas extraction more profitable and with greater speed, fuelling climate breakdown. Online social platforms are also being misused as podiums for dis/misinformation and falsehoods counter to the scientific consensus of anthropogenic climate change, allowing the digital tech sector to abdicate any social responsibility and denying the dire consequences of inaction. This review article explores the growing consumption demands and the ecological threat from digitalisation and the digital tech sector: demands that will only intensify with our insatiable appetite for digital tech services and products. Such a review aims to draw closer attention to some ways such technology can be used to assist ecological research and conservation, but also to expand upon our understanding of the negative environmental aspects of a relentless push towards a Digital Society. In uncritically accepting Big Tech’s virtuous credentials, we are choosing to ignore the immense power and influence they have over our lives, and the ways they may be propelling our environment toward collapse.